Regional Integration and Technology Diffusion : The Case of the North America Free Trade Agreement - Schiff, Maurice; Wang, Yanling (World Bank, Washington, DC, 2014)
The literature on regional integration agreements (RIAs) is vast and deals with political, economic, and political economy issues. The literature on the economics of RIAs deals mostly with static effects, and concludes that these effects are, in general, ambiguous. So far there has been no empirical analysis of the dynamic effects of RIAs based on their impact on technology diffusion from partner and nonpartner countries. Schiff and Wang's paper is a first attempt in this direction. The authors examine the impact of the North America Free Trade Agreement (NAFTA) on total factor productivity in Mexico through its impact on trade-related technology transfers from OECD countries. They estimate trade-related technology diffusion by using a measure of trade-related foreign research and development (R&D). Foreign R&D is constructed based on industry-specific R&D in the OECD, OECD-Mexico trade patterns, and input-output relations in Mexico. The authors find that: Mexico's trade with its NAFTA partners had a large and significant impact on Mexico's total factor productivity, while trade with the rest of the OECD did not. Simulating the impact of NAFTA has led to a permanent increase in total factor productivity in Mexico's manufacturing sector of between 5.5 percent and 7.5 percent and to some convergence with the economies of Canada and the United States.